Segmentation of Certificate With Connected Component Labeling Method - Jaya, Cokorda Gde Teresna; Arta Wibawa, I Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
Certificate is one of the documents that can be used as evidence of ownership or an event. For example, when certificate used as requirement to participate in an event. If a document is made as a requirement, of course the file verification process will be done. Seeing the time optimization problem when verifying the file, the authors carry out research by segmenting important data contained in a certificate as an initial step in the development of an automatic document verification system. The segmentation process carried out in this study uses the Connected Component Labeling method in determining the area to be segmented and Automatic Cropping to cut the results of the segmentation process. By using these two methods obtained an accuracy of 60% with a total of 15 pieces of test data